Comparison of dietary intake and eating behavior of professional road cyclists during training and competition - Garcia-Roves, P. M.; Terrados, N.; Fernndez, S.; Patterson, A. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2000)
The dietary intake and eating behavior of a group of professional elite road cyclists during high intensity training and competition was compared. Their eating pattern consisted of several snacks throughout the race or training, a meal eaten no later than 1 hr postexercise, supper, and breakfast. Protein intake showed a significant difference between evaluation times expressed in three ways: per total amount intake, by kg body weight, and percentage of energy supplied. Due to the high energy intake of these cyclists during training and competition (22.9 ± 1.5, 22.4 ± 1.7 MJ, respectively), they presented a high consumption of each macronutrient both in competition and in training. The eating behavior of these athletes was similar during breakfast (possib ility to choose from among approximately 25 foods) and supper (set menu), with variation in the energy intake and a similar relative contribution of the different macronutrients. In general, it is possible to consider the professional road cyclists as a homogeneous group with a similar nutrition intake, eating habits, and nutritional needs throughout the more demanding periods of the season. Furthermore, differences found in protein intake between periods could not be explained by differences in the food available in competition and training periods.